Phospholipase D activation mediates growth and migration of colon cancer cells interacting with cancer-associated fibroblasts - Majdop, Salem; Skornick, Yehuda; Avital, Shmuel; Berkovich, Liron (Cellular and Molecular Biology, 2018)
Cancer-associated fibroblasts of the stroma play a major role in tumor promoting processes. In this study we evaluated the significance of Phospholipase D (PLD) enzyme activity in promoting human colon cancer malignant potency when interacting with proximal colonic fibroblasts. Human colon cancer cell lines SW480 and HCT116, and colonic fibroblasts CCD-18Co were used as an in vitro model. PLD’s activity was measured in resting cancer cells and after culturing with fibroblasts and cancer-associated fibroblasts (CAFs) conditioned medium. The viability and migration level of the cancer cells alone and after co-culturing with fibroblast or CAFs conditioned medium were evaluated, with and without adding a PLD inhibitor. Exposure of colon cancer cells to CAFs conditioned medium significantly increased the level of PLD activity in the cancer cells (p<0.0001). Exposure of colon cancer to resting and activated fibroblast conditioned medium significantly enhanced the number of viable cancer cells as well as its migration level measured following 24 and 48 hours. Adding a PLD inhibitor significantly reduced the elevation of cell viability and migration of the colon cancer cells exposed to fibroblasts conditioned medium (p<0.005). In this in vitro model, inhibition of PLD significantly decreased proliferation and migration levels of colon cancer cells generated by stromal fibroblasts. This provides evidence that the PLD signaling pathway is directly involved in stroma-cancer interactions in the colon, thereby promoting cancer progression. Further research is needed in order to evaluate PLD as a target in colon cancer prevention or therapy.